Pengaruh Penggunaan Media Slidesgo Terhadap Kemampuan Menulis Teks Berita Pada Siswa Kelas VII SMP - Wati, Risna; Simanjuntak, Harlen; Putri, Eka (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This study aims to determine the effect of using Slidesgo media on the ability to write news texts in seventh grade students of SMP Negeri 10 Medan in the 2023/2024 academic year. This type of research is Quantitative Experimental Research with a Two Group Posttest-only research design. The population in this study were all seventh grade students with a total of 60 students determined by cluster sampling technique. The data analysis techniques used are Normality test, Homogeneity test and Hypothesis test. After conducting research for control and experimental classes using slidesgo media, the average value in the control class was 60.93 and the experimental class was 80.8. The prerequisite test results stated that the samples were Normal and Homogeneous distributed. From the results of hypothesis testing in this study, the “t” test was carried out and it was found that Thitung> Ttabel 5.0762>1.66980. Then the null hypothesis (Ho) is rejected and the hypothesis (Ha) is accepted. Thus, it can be stated that the ability to write news texts is influential using slidesgo media.